Development of a living membrane comprising a functional human renal proximal tubule cell monolayer on polyethersulfone polymeric membrane. (1st March 2015) - Schophuizen, Carolien M.S.; De Napoli, Ilaria E.; Jansen, Jitske; Teixeira, Sandra; Wilmer, Martijn J.; Hoenderop, Joost G.J.; Van den Heuvel, Lambert P.W.; Masereeuw, Rosalinde; Stamatialis, Dimitrios
Graphical abstract: Abstract: The need for improved renal replacement therapies has stimulated innovative research for the development of a cell-based renal assist device. A key requirement for such a device is the formation of a "living membrane", consisting of a tight kidney cell monolayer with preserved functional organic ion transporters on a suitable artificial membrane surface. In this work, we applied a unique conditionally immortalized proximal tubule epithelial cell (ciPTEC) line with an optimized coating strategy on polyethersulfone (PES) membranes to develop a living membrane with a functional proximal tubule epithelial cell layer. PES membranes were coated with combinations of 3, 4-dihydroxy-l -phenylalanine and human collagen IV (Coll IV). The optimal coating time and concentrations were determined to achieve retention of vital blood components while preserving high water transport and optimal ciPTEC adhesion. The ciPTEC monolayers obtained were examined through immunocytochemistry to detect zona occludens 1 tight junction proteins. Reproducible monolayers were formed when using a combination of 2 mg ml −1 3, 4-dihydroxy-l -phenylalanine (4 min coating, 1 h dissolution) and 25 μg ml −1 Coll IV (4 min coating). The successful transport of 14 C-creatinine through the developed living membrane system was used as an indication for organic cation transporter functionality. The addition of metformin or cimetidine significantly reduced the creatinine transepithelial flux, indicating active creatinine uptake in ciPTECs, most likely mediated by the organic cation transporter, OCT2 (SLC22A2). In conclusion, this study shows the successful development of a living membrane consisting of a reproducible ciPTEC monolayer on PES membranes, an important step towards the development of a bioartificial kidney.